Non-dysraphism intradural cervical lipoma - Zhao-Quan Liu; Cheng-Ta Hsieh; Jui-Ming Sun; Chih-Ta Huang (Formosan Journal of Surgery, 2021)
Intradural spinal lipomas not associated with spinal dysraphism account are rare entity. The pure cervical intradural lipomas are rarer and only eleven cases have been reported in the literature. The median age at diagnosis was 35 (8m-52y) years old and the ratio of men to female was 1.4:1. The possible risk factor included weight increase or rapid metabolic change. Only one case had recurrent condition during follow-up period. Here, we reported a 32-year-old male who presented with posterior neck pain and radiating numbness from neck to bilateral upper extremities. The radiograph of cervical spine showed a widening spinal canal diameter. Further study confirmed a pure cervical intradural intramedullary lipoma without spinal dysraphism. For preventing the neurologic deficit, early diagnosis and adequately surgical decompression were needed. Subtotal removal with cavitational ultrasonic surgical aspirator has been widely use as it minimizes any traction on already compromised neural tissues.